PELATIHAN PENGELOLAAN LIMBAH DOMESTIK MENJADI COOKIES TULANG IKAN DAN ABON IKAN JANTUNG PISANG DALAM MENDUKUNG AGRORINDUSTRI PANGAN BERKELANJUTAN DAN PROSPEKTIF DI DESA TONRONG RIJANG - Inayah, Astrina Nur; Aksan, Muhammad; Rukmelia, Rukmelia; Haryono, Iranita; Padapi, Astrini; Erwinsyah, Erwinsyah; Basri, Fitrah; YS, Al Adzim; Darwin, Ramdan; Zulaikha, Izni; Anas, Mutiara; Afifah, Nur (Jurnal Abdi Insani, 2024)
The problems that occur in the Massumpuloloe Women's Farmers Group are (1) Limited access to efficient technology for managing waste and processing food into ready-to-sell products; (2) Lack of understanding of methods for processing domestic waste into other products that can be used in agriculture; (3) Food diversification skills, namely limited knowledge about food diversification and how to process food ingredients into innovative agro-industrial products. The aim of implementing the activity is to increase public knowledge about the importance of managing domestic waste and the benefits of food diversification, as well as implementing sustainable practices that can be applied in everyday life. The method used is the counseling and training method for making (1) fish bone cookies; (2) banana flower fish floss.  The partners involved in this activity are the Massumpuloloe Farming Women's Group. The activity will be implemented on July 5 2024. The results of this activity are an increase in knowledge which can be seen from the community's activeness in the activity, as well as the number of people who take part in the activity. A follow-up plan that can be carried out is to coordinate with the village/sub-district and local government so that this activity can be carried out regularly so that access to women farmer group services for the entire community can be implemented. The conclusion is that the implementation of the activity went smoothly and the participants were very enthusiastic in taking part in the activity.